Methods of Finite Mathematics - Brown John W; Sherbert Donald R (John Wiley & Sons, 1989)
This Wiley International edition is part of a continuing program of paperbound textbooks especially designed for students and professional people overseas. Linear Methods in the Plane, Systems of Linear Equations, Matrices, Linear Programming, Methods of Counting, Methods of Probability, Probability Distributions and Statistics, Markov Analysis, Mathematics of Finance, Game Theory, Logic, Graphs, Index.